2022
DOI: 10.1177/01945998221127203
|View full text |Cite
|
Sign up to set email alerts
|

Learnings From Longitudinal Patient‐Reported and Clinical Outcomes in Palliative Head and Neck Cancer Care

Abstract: Objective Patients with palliative head and neck cancer experience many symptoms in a short period of time. Longitudinal data on patient-reported outcomes in this phase are lacking. The aim of this study is to use structurally obtained patient-reported outcome data combined with clinical patient data and obtain insight in patient-reported outcomes, survival, circumstances of death, and interventions and treatment during the palliative phase in order to improve the quality of end-of-life care and patient-center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…17,19,29 The incidence of euthanasia in the entire cohort was 5.4% (n = 70), but in people who had HNSCC as the underlying cause, it was more than 9%, which is more comparable to the 12.8% in our recent study among patients with HNSCC receiving palliative care. 30 This difference is not surprising, as previous reports also showed higher proportions of euthanasia in patients with cancer. [34][35][36] However, if compared with regional numbers, we found that there was a marginally higher rate of euthanasia among patients with HNSCC in this cohort compared with all patients with cancer in South Holland (the Netherlands).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…17,19,29 The incidence of euthanasia in the entire cohort was 5.4% (n = 70), but in people who had HNSCC as the underlying cause, it was more than 9%, which is more comparable to the 12.8% in our recent study among patients with HNSCC receiving palliative care. 30 This difference is not surprising, as previous reports also showed higher proportions of euthanasia in patients with cancer. [34][35][36] However, if compared with regional numbers, we found that there was a marginally higher rate of euthanasia among patients with HNSCC in this cohort compared with all patients with cancer in South Holland (the Netherlands).…”
Section: Discussionmentioning
confidence: 81%
“…Our previous studies among patients receiving palliative care revealed a decrease in hospital deaths from 38.0% of all patients receiving palliative care in 2008 to only 7.4% in 2020 . These results also strengthen the feasibility to reduce hospital deaths within our own curative cohort of patients (27.9%).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This phase starts when cure is no longer possible or when patients refuse curative treatment. The palliative phase is rather short, with a median survival time of 4-5 months [4][5][6]. Given the unique nature of HNC, with a wide range of speci c cancerrelated symptoms, special consideration should be given to end-of-life care [7].…”
Section: Introductionmentioning
confidence: 99%
“…We provide structural multidisciplinary care aimed at symptom regulation and psychosocial support. Since the introduction of the Expert Center, important aspects of palliative care have been improved, including enhanced doctor-patient relations, better psychosocial support, and fewer hospital admissions [5,8,9]. Further, patients are more often able to die at their preferred place, most often in their home [5,8].…”
Section: Introductionmentioning
confidence: 99%